2015
DOI: 10.1093/jat/bkv069
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Determination of Mercury in Tobacco and Mainstream Smoke from Little Cigars

Abstract: A method was developed that utilizes a platinum trap for mercury from mainstream tobacco smoke which represents an improvement over traditional approaches that require impingers and long sample preparation procedures. In this approach, the trapped mercury is directly released for analysis by heating the trap in a direct mercury analyzer. The method was applied to the analysis of mercury in the mainstream smoke of little cigars. The mercury levels in little cigar smoke obtained under Health Canada Intense smoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 22 publications
1
15
1
Order By: Relevance
“…14 Dried tobacco was analyzed for mercury using a combustion mercury analyzer as previously described 15 with minor modification. 16 Quality control was maintained throughout using Reference tobacco 1S3 (North Carolina State University, Raleigh, NC, USA) and certified reference material (CRM) CTA-OTL-1 (Instytucie Chemii i Techniki Jadrowej, Warszawa, Poland) as previously described. 14,16 Results are reported as the mean and standard deviations of 5 replicate analyses.…”
Section: Methodsmentioning
confidence: 99%
“…14 Dried tobacco was analyzed for mercury using a combustion mercury analyzer as previously described 15 with minor modification. 16 Quality control was maintained throughout using Reference tobacco 1S3 (North Carolina State University, Raleigh, NC, USA) and certified reference material (CRM) CTA-OTL-1 (Instytucie Chemii i Techniki Jadrowej, Warszawa, Poland) as previously described. 14,16 Results are reported as the mean and standard deviations of 5 replicate analyses.…”
Section: Methodsmentioning
confidence: 99%
“…However, the concern that flavorings generally recognized as safe in food products may not be as safe for inhalation 12,15 is equally valid for LCCs. Given the many LCC ingredients other than flavors already identified as harmful, or potentially harmful, [16][17][18] it is unclear whether flavor additives could present any additional, significant harm. Still, the way in which these popular flavorings are perceived by users and potential users, and the relationship between these perceptions and use, are worthy of investigation.…”
mentioning
confidence: 99%
“…The other alternative to measure the accuracy of the data is the analysis of CRMs. A large number of studies [ 45 , 47 , 55 , 56 , 58 67 ] reported the analysis of CRMs to validate their data. Regarding QC, most of the studies reported the RSD values for replicate sample analysis and/or standard materials analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Following water samples, the most frequently analyzed material for mercury was seafood samples, such as fish, shrimp, and seaweed. A few studies reported the determination of mercury in various environmental samples, such as petroleum hydrocarbons [ 88 ], human hair [ 89 , 90 ], phosphate fertilizers [ 53 ], glycerin [ 91 ], sediments [ 55 , 92 , 93 ], cosmetics [ 94 ], living cells [ 66 , 95 ], and tobacco [ 67 ]. However, a few methods [ 74 , 81 , 87 , 96 101 ] did not report their applicability to natural samples.…”
Section: Discussionmentioning
confidence: 99%